Analisis Keamanan Jaringan LAN Terhadap Kerentanan Jaringan Ancaman DDoS Menggunakan Metode Penetration - Herman Herman; Rusydi Umar; Agus Prasetyo Marsaid (STMIK Budi Darma, 2023)
At this time, there are many crimes in the internet world that cause the need for surveillance and detection of network security so that it can be anticipated quickly. The purpose of this study is to provide an analysis of the detection of network attacks located on the LAN network of the Institution's Campus . So that detection such as snort applications are needed that can detect a network attack focused on TCP, UDP, and HTTP, in order to detect instructions from the process of monitoring events that occur in a computer system or network and analyzing the possibility of an incident can recognize data packets that pass by and generate alerts according to pre-made rules. In this study using the penetration test method which is a method that aims to test the system or network security directly located and activities to evaluate the security of a computer network system. This method can also be called pentest and is usually done by pentesters at the University Institution. In this study, the use of snort can run well, because snort can detect and send alerts to administrators through applications that will be used as simulations are Drak Fantasy, Loic and Wirshak and every network